The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7759/cureus.32146
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Nutritional Parameters and Quality of Life in Patients With End-Stage Kidney Disease on In-Centre Haemodialysis in Al-Ahsa, Saudi Arabia

Abstract: Introduction: Nutrition threatens the quality of life (QOL) in end-stage kidney disease (ESKD) patients on haemodialysis (HD). The aim of the study is to assess which nutritional parameters associate with the health-related QOL category score using Arabic translated, adapted, and validated version of the Kidney Disease Quality of Life Short-Form 36 (KDQOL-36).Methods: We carried out a cross-sectional study with a total of 60 ESKD patients in one haemodialysis centre in Al-Ahsa, Saudi Arabia. The health-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…This showed that the HRQOL of dialysis patients in terms of PCS decreased along with the albumin level. This was in accordance with a prospective study, which found a statistically significant positive correlation between albumin and PCS score in dialysis patients ( 30 ). The same study also stated that hypoalbuminemia had been shown in most dialysis patients.…”
Section: Discussionsupporting
confidence: 93%
“…This showed that the HRQOL of dialysis patients in terms of PCS decreased along with the albumin level. This was in accordance with a prospective study, which found a statistically significant positive correlation between albumin and PCS score in dialysis patients ( 30 ). The same study also stated that hypoalbuminemia had been shown in most dialysis patients.…”
Section: Discussionsupporting
confidence: 93%